AGRICULTURAL BIOPRODUCTS: FUNDAMENTALS FOR THEIR PRODUCTION - Iglesias Barreto, Gabriel Alejandro; Reyes Delgado, Yosviel; Rodríguez Rico, Iván Leandro (Centro Azúcar Journal, 2025)
Introduction: The beneficial action of microorganisms and their metabolic derivatives on plants and soils is well documented, representing a highly effective alternative to the use of chemical fertilizers and pesticides. Objective: To examine the foundations for the agricultural bioproducts industrial production. Materials and Methods: Classical and updated research aimed at fermentative productions of agricultural supplies and their applications in crop fields were addressed. Results and Discussion: Products obtained from microorganisms and metabolites prove to be a highly reliable option for the management of sustainable agriculture and soils recovery. Research is mainly focused on the selection of new microorganisms with a broad action on crops and soils, more stable formulations with multipurpose functions (microbial consortia with fertilizing, pesticide and/or stimulant action in a single presentation), design of new more specific technological schemes and optimization of culture media for cell growth at higher scales. Conclusions: Although the benefits of bioproducts in agriculture have been demonstrated, market projections dictate that they have not yet displaced conventional agrochemicals, mainly due to their manufacturing cost and complexity in terms of their use. Instead, research into immobilized cell systems and fed-batch systems is essential as highly productive alternatives to traditional techniques such as submerged batch and solid-state fermentation.